Agricultural value chain development in practice: Private sector-led smallholder development - Kolavalli, Shashidhara; Mensah-Bonsu, Akwasi; Zaman, Saima (International Food Policy Research Institute, 2015)
Value chain development is adopted widely as a private sector–led approach to agricultural development that can benefit smallholders. The objective of this research is to understand how development organizations are conceptualizing and developing agricultural value chains in Ghana to include smallholders. The study is based on case studies of five programs supported by various donors. A typology is employed to categorize the intervention. Common to all the programs are interventions to encourage the development of interlinked vertical contracts between smallholders and buyers and investments to improve the operations of actors downstream. The study explores issues related to expectations, scaling up of activities to reach a significant portion of the population, technology transfer, and participatory development of value chain strategies and identifies some indicators to examine the outcomes of value chain interventions.